2016
DOI: 10.1002/pen.24264
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagrams of thermally stable, polymer‐dispersed liquid crystals: Exploring the impact of chain length and chemical structure

Abstract: Polymer-dispersed liquid crystals (PDLCs) have garnered significant interest and motivated the investigation of the phase behavior of thermally stable smectic liquid crystals (LCs) via thermally induced phase separation (TIPS). In this study, we examined a series of two, biphenyl-based smectic LCs suitable for high temperature polymer blend processing. Phase diagrams for LC/polystyrene (PS) blends at various compositions (0-60 wt%) were constructed. Less than 15 wt% of 8B8 (1,1 0 -biphenyl-4,4 0 -diyl dioctano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Even immiscible polymer blends are partially miscible with increasing ratio 11 and the miscibility (solubility) increases as a function of temperature. 24,25 As the temperature approaches the T g of blends during DSC scans, the miscibility gradually increases, thereby leading to lower T g than anticipated. There should be two T g 's for typical immiscible blends.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Even immiscible polymer blends are partially miscible with increasing ratio 11 and the miscibility (solubility) increases as a function of temperature. 24,25 As the temperature approaches the T g of blends during DSC scans, the miscibility gradually increases, thereby leading to lower T g than anticipated. There should be two T g 's for typical immiscible blends.…”
Section: Resultsmentioning
confidence: 92%
“…In addition to mechanical properties, the thermal properties of polymeric materials are of great importance due to their transition temperatures and crystallization behaviors. Even immiscible polymer blends are partially miscible with increasing ratio and the miscibility (solubility) increases as a function of temperature . As the temperature approaches the T g of blends during DSC scans, the miscibility gradually increases, thereby leading to lower T g than anticipated.…”
Section: Resultsmentioning
confidence: 93%
“…[19][20][21] LCEs can also mimic vital features of endogenous tissue thus satisfying the prerequisites biocompatibility and biodegradability, mechanical properties, cell spatial growth, cell alignment, and long-term studies that are considered as tissue engineering systems. [22][23][24] LCs have long been used and/or incorporated into materials to create composites, ensure better processing, [25][26][27][28] introduce LC properties, create chemical sensors, [29][30][31] and biosensors, 32,33 soft actuators, [34][35][36][37][38] light driven motors, 39,40 as responsive building blocks for guiding 2D cell growth, 41,42 promoters of cell orientational order, [43][44][45] or to control the dynamics of bacteria. 46,47…”
Section: Liquid Crystal Elastomers As Biomaterialsmentioning
confidence: 99%
“…[22] Liquid crystalline (LC) moieties have been introduced to polymers as promoters for better processing, or to introduce LC properties. [23][24][25][26] LC materials have thus been studied as actuators, [27−29] sensors [30−33] and biosensors, [34,35] as regulators for bacteria dynamics, [36,37] or as guides to induce 2-D cell growth. [38][39][40] Abbott and coworkers as well as Shashidhar and coworkers reported that the orientational order of LCs can be coupled to cells, making LCs promoters of cell orientational order.…”
Section: Introductionmentioning
confidence: 99%